Theranostic Nanomedicine for Malignant Gliomas - d'Angelo, Michele; Castelli, Vanessa; Benedetti, Elisabetta; Antonosante, Andrea; Catanesi, Mariano; Dominguez-Benot, Reyes; Pitari, Giuseppina; Ippoliti, Rodolfo; Cimini, Annamaria (Frontiers in Bioengineering and Biotechnology, 2019)
Brain tumors mainly originate from glial cells and are classified as gliomas. Malignant gliomas represent an incurable disease; indeed, after surgery and chemotherapy, recurrence appears within a few months, and mortality has remained high in the last decades. This is mainly due to the heterogeneity of malignant gliomas, indicating that a single therapy is not effective for all patients. In this regard, the advent of theranostic nanomedicine, a combination of imaging and therapeutic agents, represents a strategic tool for the management of malignant brain tumors, allowing for the detection of therapies that are specific to the single patient and avoiding overdosing the non-responders. Here, recent theranostic nanomedicine approaches for glioma therapy are described.